Assesment of spatial dynamics of COVID-19 in the territory of the Russian Federation in 2020–2023 - N. V. Yuminova; N. A. Kontarov; E. I. Kontarov (Журнал инфектологии)
SARS-CoV-2 virus, first isolated in China in 2019, launched an epidemic and paralysed global health care in just a few mounth. In this article we present the results of a mathmatical analysis of data on morbidity for COVID-19 in Russia in 2020–2023. The structural characteristics of morbidity from this disease for the population of Moscow, St. Petersburg and Sevastopol are given based on the calculation of the Ryabtsev coefficient. The territorial concentration of morbidity in Russia was assessed dynamicaly by calculating the Herfindahl-Hirshman index.